Stable Radicals 2010
DOI: 10.1002/9780470666975.ch8
|View full text |Cite
|
Sign up to set email alerts
|

Metal Coordinated Phenoxyl Radicals

Abstract: The term "phenoxyl" radical was first introduced in 1914 by Pummerer 1 to designate species involved in the oxidation of naphthols and phenanthroles. It was not until the 1960s that the existence of phenoxyls was demonstrated by Electron Paramagnetic Resonance (EPR). The term "stable" is commonly used to designate radicals such as nitroxides, trityls, and so on. Although the term "stable" had been associated with some phenoxyl radicals in 1967, 2 it must be realized that phenoxyl radicals exhibiting stabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 146 publications
0
10
0
Order By: Relevance
“…The τ 4 index is somewhat larger (0.31), disclosing significant tetrahedral distortions at the metal center, which are confirmed by O1–Cu–N2 and O2–Cu–N1 angles of 158°. Finally, the O1–C1 and O2–C13 bond distances in both 3 and 4 are 1.302–1.309(3) Å, as observed in related copper-phenolate complexes. ,,,,, , …”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…The τ 4 index is somewhat larger (0.31), disclosing significant tetrahedral distortions at the metal center, which are confirmed by O1–Cu–N2 and O2–Cu–N1 angles of 158°. Finally, the O1–C1 and O2–C13 bond distances in both 3 and 4 are 1.302–1.309(3) Å, as observed in related copper-phenolate complexes. ,,,,, , …”
Section: Resultsmentioning
confidence: 60%
“…Both the increased metal charge and the orthogonality between the peripheral rings likely contribute to the localization of the radical on one arm of the ligand, in contrast to the above copper-phenoxyl complexes. A further consequence is a lack of specific NIR signature for the radical complex, whose vis-NIR spectrum compares with that of isolated phenoxyl radicals …”
Section: Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of model studies of GO have been reported with emphasis on the characteristic electronic structure of copper(II)-phenoxyl radical and its reactivity [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Copper(II)-phenoxyl radical complexes have quite different geometric and electronic structures compared with the copper(III)-phenolate species, which is the same one-electron oxidized form of the copper(II)-phenolate species [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%